2013
DOI: 10.1007/978-3-642-37374-9_101
|View full text |Cite
|
Sign up to set email alerts
|

Wheel of B2C E-commerce Development in Saudi Arabia

Abstract: Online retailing (a model of B2C e-commerce) is growing worldwide, with companies in many countries showing increased sales and productivity as a result. It has great potential within the global economy. This paper looks at the current status of online retailing in Saudi Arabia, with particular focus on what inhibits or enables both the customers and retailers. It also analyses the status of Government involvement and proposes a layered model, known as the "Wheel of Online Retailing" which illustrates how Gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Our study provided the contribution in terms of novel B2C model that will help in improving processes required for understanding of design of e-commerce websites and improve the features that will help in gaining market orientation information service quality. Moreover, the analyses in terms of descriptive statistics reveal that the proposed trust model produces an excellent performance for the factors that are closely related to the identified requirements in comparison to the work given in [14]. All the components of the model are found responsible for enhancing the level of trust in e-commerce websites in Saudi Arabia with a significance level of 0.01.…”
Section: Significance Levelmentioning
confidence: 82%
See 2 more Smart Citations
“…Our study provided the contribution in terms of novel B2C model that will help in improving processes required for understanding of design of e-commerce websites and improve the features that will help in gaining market orientation information service quality. Moreover, the analyses in terms of descriptive statistics reveal that the proposed trust model produces an excellent performance for the factors that are closely related to the identified requirements in comparison to the work given in [14]. All the components of the model are found responsible for enhancing the level of trust in e-commerce websites in Saudi Arabia with a significance level of 0.01.…”
Section: Significance Levelmentioning
confidence: 82%
“…Moreover, the law for Internet business in the nation is fairly dark. Although Saudi Arabia significantly adds to the endeavors of the United Nations Commission into International Trade Laws [14], more activities are important to fortify the online business for quick monetary turn of events.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, customer' readiness for change is one of the obstacles facing entrepreneurs and affecting their decision to launch their products and services online. According to AlGhamdi et al (2013), customers complain about the dearth of online retailers, whereas retailers claim that the low number of online customers impedes them from investing in online stores.…”
Section: E-commerce In Saudimentioning
confidence: 99%
“…Both literature and ARABNET 2014 conference presentations informed that government support is an important factor impacting e-commerce entrepreneurial adoption in the Saudi Arabia. Several scholars highlighted that the number of government research institutions and organisations supporting e-commerce and entrepreneurship in Saudi Arabia are still limited (Khan, 2013;Al-Hudhaif, 2011;AlGhamdi et al, 2013). They suggested that the Saudi…”
Section: Government Supportmentioning
confidence: 99%